Endothelial cell‐derived angiopoietin‐2 is a therapeutic target in treatment‐naive and bevacizumab‐resistant glioblastoma. Issue 1 (14th December 2015) - Scholz, Alexander; Harter, Patrick N; Cremer, Sebastian; Yalcin, Burak H; Gurnik, Stefanie; Yamaji, Maiko; Di Tacchio, Mariangela; Sommer, Kathleen; Baumgarten, Peter; Bähr, Oliver; Steinbach, Joachim P; Trojan, Jörg; et al.
Abstract: Glioblastoma multiforme (GBM) is treated by surgical resection followed by radiochemotherapy. Bevacizumab is commonly deployed for anti‐angiogenic therapy of recurrent GBM; however, innate immune cells have been identified as instigators of resistance to bevacizumab treatment. We identified angiopoietin‐2 (Ang‐2) as a potential target in both naive and bevacizumab‐treated glioblastoma. Ang‐2 expression was absent in normal human brain endothelium, while the highest Ang‐2 levels were observed in bevacizumab‐treated GBM. In a murine GBM model, VEGF blockade resulted in endothelial upregulation of Ang‐2, whereas the combined inhibition of VEGF and Ang‐2 leads to extended survival, decreased vascular permeability, depletion of tumor‐associated macrophages, improved pericyte coverage, and increased numbers of intratumoral T lymphocytes. CD206 + (M2‐like) macrophages were identified as potential novel targets following anti‐angiogenic therapy. Our findings imply a novel role for endothelial cells in therapy resistance and identify endothelial cell/myeloid cell crosstalk mediated by Ang‐2 as a potential resistance mechanism. Therefore, combining VEGF blockade with inhibition of Ang‐2 may potentially overcome resistance to bevacizumab therapy. Synopsis: While recurrent glioblastoma is treated by inhibiting angiogenesis, resistance limits therapeutic efficacy. Angiopoietin‐2 (Ang‐2), a potent endothelium‐derived angiogenesis factor and regulator of myeloid cell infiltration, is a therapeutic target for treating naive and bevacizumab‐resistant glioblastoma. The therapeutic benefit of co‐targeting Ang‐2 and VEGF signaling (using AMG386 and aflibercept/VEGF‐trap) is shown in mouse models of GBM. Ang‐2 and VEGF combination therapy decreased GBM angiogenesis and permeability, improved vascular maturation, and limited the number of tumor‐associated macrophages. Numbers of CD206 + (M2‐like) macrophages remained high upon therapy, suggestive of subsequent targeting of M2‐like macrophages in bevacizumab‐resistant GBM. Inhibition of Ang‐2, either alone or in combination with VEGF inhibition is of potential use to overcome resistance in GBM patients that have failed bevacizumab therapy. Abstract : While recurrent glioblastoma is treated by inhibiting angiogenesis, resistance limits therapeutic efficacy. Angiopoietin‐2 (Ang‐2), a potent endothelium‐derived angiogenesis factor and regulator of myeloid cell infiltration, is a therapeutic target for treating naive and bevacizumab‐resistant glioblastoma.